INCOME DISTRIBUTION AND TRADE POLICY - Akbarova , Mohinur Farxod qizi (GOLDEN BRAIN, 2024)
Income distribution is a critical issue that has garnered significant attention from policymakers, economists, and the general public in recent years. The distribution of income within a country can have profound implications for economic growth, social stability, and overall well-being. Trade policy, on the other hand, plays a significant role in shaping the distribution of income by influencing factors such as wages, employment levels, and the prices of goods and services. Therefore, understanding the relationship between income distribution and trade policy is crucial for designing effective policy interventions that can promote both economic growth and equity. This research aims to explore the complex interplay between income distribution and trade policy, shedding light on how trade policies can either exacerbate or mitigate income inequality within a country. By examining the empirical evidence and theoretical framework surrounding this issue, this study seeks to provide valuable insights for policymakers seeking to promote more equitable economic outcomes through trade policy.